Risk of Heart Failure Hospitalization Associated With Cilostazol in Diabetes: A Nationwide Case–Crossover Study - Wu, Cho-Kai; Lin, Jou-Wei; Wu, Li-Chiu; Chang, Chia-Hsuin (Frontiers in Pharmacology, 2019)
Background and Objective: It has been suggested to avoid cilostazol, the first-line therapy for peripheral arterial disease, in patients with congestive heart failure. The objective of this study was to evaluate the risk of hospitalization for heart failure (HHF) associated with cilostazol use in the patients of diabetes mellitus. Methods: This case-crossover study retrieved records on diabetic patients > 20 years of age who were hospitalized for heart failure during the period of 2009-2011 from the Taiwan National Health Insurance Database. The “current” period was defined as 1-30 days prior to HHF whereas the 91-120 days prior to HHF served as the “reference” period. The exposure status just preceding the event is compared with exposure of the same person in one or more referent remote to the event. Adjusted odds ratios (OR) were used to estimate time-varying discordant exposure by the ratio of the number exposed to cilostazol only during the case period to the number exposed to cilostazol only during the control period. Results: A total of 47,506 diabetic patients were included in the analysis (average age: 72.7±12.4, percentage of males: 48%). A total of 399 patients (0.84%) received cilostazol only in the current period, and 252 (0.53%) received cilostazol only in the reference period. After adjustment for other medications, a significant association was found between cilostazol and HHF (OR: 1.35, 95% CI: 1.14-1.59). After further adjustment for time-varying co-morbidities the ORs remained essentially the same. Sensitivity analyses using different definitions of control period (ranging from 31-60 days, 61-90 days, to 121-150 days before index date) yielded adjusted ORs of 1.43 (95% CI: 1.14-1.79), 1.31 (95% CI: 1.09-1.57) and 1.23 (95% CI: 1.06-1.44), respectively suggesting the robustness of our study findings. Conclusion: Use of cilostazol may be positively related to the risk of HHF. Further studies are warranted to explore the underlying mechanisms and to confirm the association.